Estimation of Conductivity in Liquids and a System to Compensate it - Daunoras, J.; Knyš, A. (Elektronika ir Elektrotechnika, 2005)
In this paper an estimation of milk conductivity and correction of prediction of milk freezing point is discussed. An method of milk freezing point prediction according to milk quantitative analysis (contents of fat, proteins and lactose in milk) and conductivity is surveyed. The reliance between milk conductivity and temperature of the sample is analyzed. The experimental schematics and results are presented. The dependence of prediction of milk freezing point and the temperature of the sample is simulated, the modeling schematics is presented. The experimental data of the system for prediction of milk freezing point with compensation for the sample temperature changes and data analysis are presented. Ill.9, bibl.7 (in Lithuanian; summaries in Lithuanian, English, Russian).